Ketamine Modulates Zic5 Expression via the Notch Signaling Pathway in Neural Crest Induction - Shi, Yu; Li, Jiejing; Chen, Chunjiang; Xia, Yongwu; Li, Yanxi; Zhang, Pan; Xu, Ying; Li, Tingyu; Zhou, Weihui; Song, Weihong (Frontiers in Molecular Neuroscience, 2018)
Ketamine is a potent dissociative anesthetic and the most commonly used illicit drug. Many addicts are women at childbearing age. Although ketamine has been extensively studied as a clinical anesthetic, its effects on embryonic development are poorly understood. Here, we applied the Xenopus model to study the effects of ketamine on development. We found that exposure to ketamine from pre-gastrulation (stage7) to early neural plate (stage13.5) resulted in disruption of neural crest derivatives. Ketamine exposure did not affect mesoderm development as indicated by the normal expression of Chordin, Xbra, Wnt8 and Fgf8. However, ketamine treatment significantly inhibited Zic5 and Slug expression at early neural plate stage. Overexpression of Zic5 rescued ketamine-induced Slug inhibition, suggesting the blockage of neural crest induction was mediated by Zic5. Furthermore, we found Notch signaling was altered by ketamine. Ketamine inhibited the expression of Notch targeted genes including Hes5.2a, Hes5.2b and ESR1 and ketamine-treated embryos exhibited Notch-deficient somite phenotypes. A 15bp core binding element upstream of Zic5 was induced by Notch signaling and caused transcriptional activation. These results demonstrated that Zic5 works as a downstream target gene of Notch signaling in Xenopus neural crest induction. Our study provides a novel teratogenic mechanism whereby ketamine disrupts neural crest induction via targeting a Notch-Zic5 signaling pathway.